Print Media Coverage of Nana Konadu Agyeman Rawlings as a Presidential Candidate in 2011 - Fofie, I.M. (University of Ghana, 2016)
This study is a quantitative content analysis of the coverage of Nana Konadu Agyeman Rawlings when she contested the then sitting president, Professor John Evans Atta Mills in 2011, for the right to lead the NDC party in the 2012 elections. Using the framing theory and liberal feminists theory as the theoretical framework, the study investigated how four newspapers — the Daily Graphic, the Daily Guide, the Ghanaian Times and the Chronicle— covered Nana Konadu Agyeman Rawlings as compared to John Evans Atta Mills during the 2011 primaries of the NDC. The objective of the study was to see whether there was gender bias in reportage as identified in previous research from other contexts. The study was particularly interested in the quantity, quality and tone of coverage. A census of the four newspapers published between 1st February and 31st July, 2011 was used. These marked the month in which Agyeman Rawlings announced her intention to contest and the month she lost to Atta Mills. Two data sets were used. The first data set was used to compare coverage that Agyeman Rawlings received versus that of Atta Mills during the primaries. The second data set was focused on Agyeman Rawlings and did not compare to Atta Mills. In all, 377 stories from the four newspapers were content analysed for the first data set and 246 stories for the second data set. Findings from the study showed that in terms of quantity of coverage, Agyeman Rawlings received an almost equal amount of coverage to Atta Mills with slight differences that favoured her. The study also found that although there was not much difference in quality of coverage for both candidates, there were gender biases in favour of Atta Mills. This confirmed liberal feminists‘ assertion of gender bias in the news against female candidates. Not surprisingly and consistent with the literature the news media employed the use of the ‗first woman‘ frame significantly in presenting Agyeman Rawlings‘ candidacy. However, contrary to the dominant literature, the tone of coverage was neutral and not negative for Agyeman Rawlings
Thesis (MPhil.)
Keywords: Presidential Candidate; Print Media; Elections; Ghana